DESAIN BUKU CERITA ANAK BERGAMBAR BERBASIS PENDIDIKAN KARAKTER ANTIKORUPSI PADA PEMBELAJARAN TEMATIK DI MADRASAH IBTIDAIYAH: DESAIN BUKU CERITA ANAK BERGAMBAR BERBASIS PENDIDIKAN KARAKTER ANTIKORUPSI PADA PEMBELAJARAN TEMATIK DI MADRASAH IBTIDAIYAH - Maulida, Syafa’atul; Al Ta'dib, Evita (Al Tadib : Jurnal Ilmu Pendidikan, 2020)
Abstract: Anti-corruption education as one of character education that needs to be applied to elementary school-age children as a form of prevention in handling corruption cases that often occur in Indonesia. Considering that in 2018, Indonesia's GPA is still ranked 89 out of 180 countries in the world. Meanwhile there are still many school institutions that have not implemented anti-corruption education specifically. So in this study, researchers developed learning resources and media in the form of picture books based on anti-corruption education. Picture books are integrated with thematic learning materials for grade IV Madrasah Ibtidaiyah. This research uses the R & D (Research and Development) method. This research model values the development design of Dick and Carey, by taking 9 stages including: Analysis of general learning objectives, Conducting learning analysis, Recognizing student behavior and characteristics, Formulating specific learning objectives, Developing benchmark reference test items, Developing learning strategies, Selecting and develop learning materials, design and carry out formative evaluations, revise learning materials. Based on product development, the validation results obtained are: the validation of the material experts got a score of 96% with very decent criteria, the validation of learning design experts got a score of 84% with decent criteria, and the validation of learning experts got a score of 91.7% with very decent criteria. Product attractiveness testing based on assessment and student responses scored 87.9% with very interesting criteria.